Responses of ‘Carabao’ mango to various ripening agents - Lacap, Angelyn T.; Bayogan, Emma Ruth V.; Secretaria, Leizel B.; Lubaton, Christine Diana S.; Joyce, Daryl C. (2019)
Calcium carbide (CaC2) reacts with moisture in the air to produce acetylene (C2H2) gas, an analog of ethylene (C2H4). Commercial sources of CaC2 may be contaminated with arsenic and phosphorous, which are also released during a chemical reaction. This constitutes a potentially serious health risk to ripeners and may contaminate the product. Although banned in many countries, CaC2 is still used in the Philippines because equally inexpensive and effective alternatives are lacking. This study investigated the relative efficacy of alternatives for ripening ‘Carabao’ mango. Fruit harvested at 107 d after flower induction were treated with CaC2 (2.5, 5.0, or 7.5 g kg–1); ethephon (500, 1000, or 1500 μL L–1); Gliricidia sepium leaves (20% w/w); or ‘Cardava’ banana fruit (10% w/w) for 72 h. Mangoes were then held under ambient room conditions [29.9 ± 3.1°C, 77.74 ± 2.9% relative humidity (RH)] for 7 d. Assessments of peel color, firmness, and total soluble solids showed that fruit treated with higher concentrations of ethephon (1000 or 1500 μL L–1) exhibited similar ripening responses as those treated with CaC2. Application of 500 μL L–1 ethephon and the bioethylene sources G. sepium and ‘Cardava’ banana did not effectively ripen ‘Carabao’ mango as compared to the other treatments. The effectiveness of CaC2 did not vary between the concentrations tested. Just 2.5 g kg–1 was needed to ripen the fruit, which is considerably less than the commercial practice of using 10 g kg–1. Weight loss was highest in mangoes treated with CaC2 or ethephon. Similar to CaC2, ethephon treatment (1000 or 1500 μL L–1) reduced the time to reach saleability to 3–4 d as compared to 6 d for untreated mangoes. Accordingly, 1000 μL L–1 ethephon could be a relatively safer alternative to CaC2 in ripening ‘Carabao’ mango. Moreover, the benefits of using ethephon over conventional CaC2 include lower cost and higher profit.
Keywords: Mango; Mango--Varieties.